Utilização da técnica da reflectometria no domínio do tempo para medidas de condutividade elétrica aparente de um solo - Oro, Alice Leal Terres (2006)
Measurements of solute concentrations at soils are essential to optimize irrigation and fertilizer application, to study surface runoff and erosion and to evaluate soil salinity. For this purpose, Time Domain Reflectometry is a dielectric technique that has been shown to give accurate water content and electrical conductivity values. Used under both laboratory and field conditions, this a non-destructive essay takes simultaneous measurements of electrical conductivity and soil water content, using a single probe and testing only one sample region. Although there are many ways in which electrical conductivity may be obtained with Time Domain Reflectometry equipment, few of them are characterized by simplicity and straight forwardness. Because of that, this study aimed to evaluate different methods to determine electrical conductivity at solutions and soils. A sequence of laboratory experiments was conducted in deformed soil samples of an Oxisol from West Parana State, arranged in columns 0,30 m height, with an internal diameter of 0,19 m. The three wire probes, with manual assembling and without impedance-matching transformer, were vertically installed in soil columns, considering as a control one the column which soil received only distilled water. The others treatments were defined according to the sodium chloride content: 0,01; 0,03; 0,05; 0,07; 0,09; 0,10 and 0,15 N. The electrical conductivity was determined using waveforms collected with specific software and there wasn t signal attenuation. It was found a linear relationship between the bulk electrical conductivity and the pore water electrical conductivity under constant water content. It was concluded that soils with significant iron contents display an atypical dielectric behavior that limits the applicability of the equipment for measuring not only soil moisture but bulk electrical conductivity also.